Diagnosis patterns of sickle cell disease in Ghana: a secondary analysis - Sims, Alexandra M.; Bonsu, Kwaku Osei; Urbonya, Rebekah (BMC Public Health, 2021)
Background: Despite having the highest prevalence of sickle cell disease (SCD) in the world, no country in Sub Saharan Africa has a universal screening program for the disease. We sought to capture the diagnosis patterns of SCD (age at SCD diagnosis, method of SCD diagnosis, and age of first pain crisis) in Accra, Ghana. Methods: We administered an in-person, voluntary survey to parents of offspring with SCD between 2009 and 2013 in Accra as a part of a larger study and conducted a secondary data analysis to determine diagnosis patterns. This was conducted at a single site: a large academic medical center in the region. Univariate analyses were performed on diagnosis patterns; bivariate analyses were conducted to determine whether patterns differed by participant’s age (children: those < 18 years old whose parents completed a survey about them, compared to adults: those > = 18 years old whose parents completed a survey about them), or their disease severity based on SCD genotype. Pearson’s chi-squared were calculated. Results: Data was collected on 354 unique participants from parents. Few were diagnosed via SCD testing in the newborn period. Only 44% were diagnosed with SCD by age four; 46% had experienced a pain crisis by the same age. Most (66%) were diagnosed during pain crisis, either in acute (49%) or primary care (17%) settings. Children were diagnosed with SCD at an earlier age (74% by four years old); among the adults, parents reflected that 30% were diagnosed by four years old (p < 0.001). Half with severe forms of SCD were diagnosed by age four, compared to 31% with mild forms of the disease (p = 0.009). Conclusions: The lack of a robust newborn screening program for SCD in Accra, Ghana, leaves children at risk for disease complications and death. People in our sample were diagnosed with SCD in the acute care setting, and in their toddler or school-age years or thereafter, meaning they are likely being excluded from important preventive care. Understanding current SCD diagnosis patterns in the region can inform efforts to improve the timeliness of SCD diagnosis, and improve the mortality and morbidity caused by the disease in this high prevalence population.
Keywords: sickle cell disease; Ghana; newborn; pain; ACE: Genetic Medicine; WAGMC; University of Ghana; Fatimah Farooq; Fitz Tavernier